Pengaruh Penggunaan Modul Pembelajaran Sistem Koloid Berbasis Model Differentiated Science Inquiry terhadap Hasil Belajar Kognitif Peserta Didik - Wijaya M, Mohammad (Program Pasca Sarjana UNM, 2022)
This study is an experimental study (quasi experiment) which aims to determine the effect of the use of learning modules based on the differentiated science inquiry model on cognitive learning outcomes of students in Class XI MIPA 1 SMAN 8 Gowa on colloidal system material. The design of this study using pretest-posttest control group design. The results of the analysis of the description obtained that the average value of the experimental class and control class learning outcomes of 89.65 and 81.43 with a standard deviation of 3.96 and 5.38, respectively. Completeness of learning experimental class reached 94.44% while the control class was only 91.67%. The difference in the value of N-Gain category for each level of inquiry also occurs where the N-Gain in, SI, GI, and SDI in the control and experimental classes are successively 0.696 (medium); 0.821 (high); 0.771 (high); 0.863 (high); 0.78 (high); 0.885 (high); 0.789 (high) and 0.884 (high). The average cognitive learning outcomes of students who are taught by using learning modules based on the DSI model is higher than the DSI learning model without using learning modules. The results of hypothesis testing with Mann Whitney Test at a significant level, α = 0,05 obtained significance (0.000) so that it is concluded that there is an influence of the use of learning modules based on the DSI model on cognitive learning outcomes of students.